Washback Effects of Summative English Test on Teaching Practices in EFL Classrooms: Teachers’ Perspectives - Putri Alfiana Amalia; Muhammad Farkhan; Nida Husna; Teguh Khaerudin (Universitas Cokroaminoto Palopo, 2026)
This study explores the perception of two secondary school EFL teachers towards the washback effect of summative English tests on their teaching practices. Employing a qualitative descriptive design with purposive sampling, data were collected through semi-structured interviews and analyzed using the Miles, Huberman, and Saldana (2014) interactive model, comprising data condensation, data display, and conclusion drawing and verification. Given the exploratory nature of this study and its limited number of participants, the findings are not intended for generalization but to offer contextual insights into how teachers interpret and respond to assessment demands in their daily classroom practices. The findings reveal that the summative English test shaped teachers’ instructional decisions, material selection, classroom activities, and time allocation before the examination. Both positive and negative washback were identified. Positive washback appeared in the form of increased student motivation, learning focus, familiarity with the test formats, material reinforcement, and formative feedback. Negative washback manifested as skills narrowing, particularly the marginalization of speaking and listening teaching to the test, score orientation, and student anxiety. Importantly, the findings suggest that washback is not mechanically produced by the test itself but is mediated by teachers’ pedagogical responses, including their choices of material, assessment media, and strategies for managing student pressure. These findings contribute to washback scholarship by foregrounding the teacher’s mediating role in the context of regular classroom summative tests, a dimension that remains underexplored compared to high-stakes national or international examinations.